Justice court versus social media court - Syarofi, Syarofi (Privietlab, 2025)
The development of digital technology, particularly social media, has significantly transformed the dynamics of Indonesia’s criminal justice system. Social media now functions as a public platform that shapes public opinion even before formal legal proceedings commence, giving rise to the phenomenon of